Standarisasi Parameter Spesifik Dan Non Spesifik Ekstrak Etil Asetat Daun Beluntas (Pluchea indica L.) - Sholikhah Deti Andasari; Choiril Hana Mustofa; Eka Oktavia Arabela (CERATA Jurnal Ilmu Farmasi, 2021)
Traditionally, the leaves of Beluntas (Pluchea indica L.) are used as medicine to eliminate body odor, as a fever reducer (antipyretic), increase appetite (stomakik), laxative sweat (diaphoretic), pain, diarrhea and vaginal discharge. The need to determine the quality standard of the extract from a review of specific and non-specific parameters of the ethyl acetate extract of the leaves of beluntas (Pluchea indica L). The extract was made by maceration method using ethyl acetate and the quality standard was determined by determining specific parameters including extract identity, extract organoleptic and soluble compounds in ethyl solvent and phytochemical screening. Non-specific parameters which include drying shrinkage, specific gravity and moisture content. The results of the observation of specific parameters obtained the identity of the thick extract, blackish green color, characteristic aromatic odor and bitter taste. The content of the soluble compound in ethanol is 22.201%±2.163. The content of water-soluble compounds was 24.578% ± 2.326. Identification of the chemical content of the extract was positive for flavonoid compounds, tannins and saponins, and negative for alkaloid compounds. Moisture content 15,878±2,087. Drying shrinkage 20.895% ± 3.674. Specific gravity 0.668 g/mL ± 0.355.